Shifting Under Pressure: Timing Practices within Regulatory Information Disclosure Programs - Vinit Desai (American Business Review)
Research examines the process through which regulatory agencies and other powerful third parties publicly disseminate information about organizations in order to reduce the information asymmetry between those organizations and their dispersed or less powerful stakeholders. These disclosure programs are presumed to work by mobilizing stakeholders to pressure organizations for change. Prior studies focus on organizations’ resistance to that external pressure, often drawing from theories of institutional forces and organizational legitimacy. Instead, the present study examines the public disclosure process itself, and adapts research on organizational learning and collective attention focus to develop new theory regarding how organizations may selectively time their practices to influence these disclosures in their favor. Results suggest that organizations may respond to disclosure programs and other governance structures when actively monitored, but may drift out of compliance during intervening periods. Findings also suggest that strong governance outside of the regulatory disclosure process can help to reduce these problems. The study contributes to corporate governance, organizational learning, and other literatures by developing new theory regarding the timing of organizational responses to regulatory interventions, and by providing evidence that overlapping forms of oversight may mitigate the limitations within any one particular governance mechanism.